Three Dimensional Visualization of Human Cardiac Conduction Tissue in Whole Heart Specimens by High-Resolution Phase-Contrast CT Imaging Using Synchrotron Radiation. (November 2016) - Shinohara, Gen; Morita, Kiyozo; Hoshino, Masato; Ko, Yoshihiro; Tsukube, Takuro; Kaneko, Yukihiro; Morishita, Hiroyuki; Oshima, Yoshihiro; Matsuhisa, Hironori; Iwaki, Ryuma; Takahashi, Masashi; Matsuyama, Takaaki; et al.
Background: The feasibility of synchrotron radiation-based phase-contrast computed tomography (PCCT) for visualization of the atrioventricular (AV) conduction axis in human whole heart specimens was tested using four postmortem structurally normal newborn hearts obtained at autopsy. Methods: A PCCT imaging system at the beamline BL20B2 in a SPring-8 synchrotron radiation facility was used. The PCCT imaging of the conduction system was performed with "virtual" slicing of the three-dimensional reconstructed images. For histological verification, specimens were cut into planes similar to the PCCT images, then cut into 5-μm serial sections and stained with Masson's trichrome. Results: In PCCT images of all four of the whole hearts of newborns, the AV conduction axis was distinguished as a low-density structure, which was serially traceable from the compact node to the penetrating bundle within the central fibrous body, and to the branching bundle into the left and right bundle branches. This was verified by histological serial sectioning. Conclusion: This is the first demonstration that visualization of the AV conduction axis within human whole heart specimens is feasible with PCCT.